Design, synthesis and biological evaluation of (E)-5-styryl-1,2,4-oxadiazoles as anti-tubercular agents - Upare, Abhay Atmaram; Gadekar, Pradip K.; Sivaramakrishnan, H.; Naik, Nishigandha; Khedkar, Vijay M.; Sarkar, Dhiman; Choudhari, Amit; Roopan, S. Mohana (Bioorganic Chemistry, 2019)
Cinnamic acid and its derivatives are known for anti-tubercular activity. The present study reports the synthesis of cinnamic acid derivatives via bioisosteric replacement of terminal carboxylic acid with ``oxadiazole''. A series of cinnamic acid derivatives (styryl oxadiazoles) were designed and synthesized in good yields by reaction of substituted cinnamic acids (2, 15a-15s) with amidoximes. The synthesized styryl oxadiazoles were evaluated in vitro for anti-tubercular activity against Mycobacterium tuberculosis (Mtb) H37Ra strain. The structure-activity relationship (SAR) study has identified several compounds with mixed anti-tubercular profiles. The compound 32 displayed potent anti-tubercular activity (IC50= 0.045 mu g/mL). Molecular docking studies on mycobacterial enoyl-ACP reductase enzyme corroborated well with the experimental findings providing a platform for structure based hit-to-lead development.
Keywords: 1; 2; 4-Oxadiazole; Anti-tubercular; Bioisosteres; Cinnamic acid; Molecular docking